Blood–brain barrier: a real obstacle for therapeutics - Shiekh FA (Dove Medical Press, 2012)
Farooq A ShiekhAix-Marseille Université, URMITE, UMR, CNRS 7278, IRD 198, Marseille, FranceIn a recent report published in the International Journal of Nanomedicine, Gulati et al1 have described the most innovative study addressing an important issue of the "blood–brain barrier," which can act as a barrier to one of the fundamental goals of modern neurobiology that would have a direct impact on highly debated future therapeutics for both brain cancer and neurological disorders. Contrary to what has been the case with conventional therapy, the authors were able to completely bypass the blood–brain barrier (Figure 1) – a limiting factor for efficient drug delivery – by proposing a new, alternative approach using nanoengineered TNT/Ti implants for local delivery of chemotherapeutics such as doxorubicin into the brain. There must be millions of good drugs sitting in pharmaceutical company stores that cannot be delivered simply because they cannot get past the blood–brain barrier.2 This is an area that has been under-researched and its significance has not yet been recognized. Neuroscience textbooks bury this issue in the appendix, PhD programs give it a cursory treatment, and pharmaceutical companies have tried to ignore it. Despite the blood–brain barrier acting as a stubbornly real obstacle for potential drugs to be used against many disorders of the central nervous system, the field of drug delivery is advancing rapidly. View original paper by Gulati and colleagues.